Answer:
Option B is the correct answer.
Step-by-step explanation:
[tex]f(x)=27\bigg(\frac{1}{3}\bigg)^x[/tex] matches the table.
• When x = 0
[tex]\implies f(x)=27\bigg(\frac{1}{3}\bigg)^0= 27*1=27[/tex]
•When x = 1
[tex]\implies f(x)=27\bigg(\frac{1}{3}\bigg)^1= 27*\frac{1}{3}=9[/tex]
•When x = 2
[tex]\implies f(x)=27\bigg(\frac{1}{3}\bigg)^2= 27*\frac{1}{9}=3[/tex]
•When x = 3
[tex]\implies f(x)=27\bigg(\frac{1}{3}\bigg)^3= 27*\frac{1}{27}=1[/tex]
•When x = 4
[tex]\implies f(x)=27\bigg(\frac{1}{3}\bigg)^4= 27*\frac{1}{81}=\frac{1}{3}[/tex]